Phylogeny and Integrative Taxonomy of the Genera Gymnaetoides and Pseudotachycines (Orthoptera: Rhaphidophoridae) - Qidi Zhu; Haijian Wang; Zhijun Zhou; Fuming Shi (Insects, 2022)
The genera Gymnaetoides and Pseudotachycines are endemic to China and are morphologically homogeneous. The few available diagnostic characters make species identification particularly challenging. Species cannot be classified according to the given generic diagnosis, and phylogenetic analyses have not been reported. Here, we reconstruct the phylogeny using Bayesian inference and maximum likelihood and employ four approaches to delimit species. The results suggest that both Gymnaetoides and Pseudotachycines are paraphyletic. Therefore, we revise their taxonomy based on the combination of morphological characters and molecular data. A new genus Homotachycines Zhu & Shi gen. nov. is erected, and six new combinations are proposed. Species delimitation identifies 15 new species and one new subspecies: Gymnaetoides huangshanensis, G. petalus, G. yangmingensis, G. lushanensis, Pseudotachycines procerus, P. procerus guizhouensis, P. zhengi, P. nephrus, P. sagittus, P. fengyangshanensis, Homotachycines triangulus, H. quadratus, H. baokangensis, H. fusus, H. concavus, and H. qinlingensis sp. nov. Moreover, we find that the shapes of the dorsal lateral lobes and the dorsal median lobe of the male genitalia are also important characters for identifying these genera and that the shapes of the dorsal and lateral sclerites of the male genitalia are suitable for the classifications of species.